An adiponectin-S1P autocrine axis protects skeletal muscle cells from palmitate-induced cell death - Botta, Amy (Lipids Health Dis, 2020)
BACKGROUND: The prevalence of type 2 diabetes, obesity and their various comorbidities have continued to rise. In skeletal muscle lipotoxicity is well known to be a contributor to the development of insulin resistance. Here it was examined if the small molecule adiponectin receptor agonist AdipoRon mimicked the effect of adiponectin to attenuate palmitate induced reactive oxygen species (ROS) production and cell death in L6 skeletal muscle cells. METHODS: L6 cells were treated ±0.1 mM PA, and ± AdipoRon, then assays analyzing reactive oxygen species (ROS) production and cell death, and intracellular and extracellular levels of sphingosine-1 phosphate (S1P) were conducted. To determine the mechanistic role of S1P gain (using exogenous S1P or using THI) or loss of function (using the SKI-II) were conducted. RESULTS: Using both CellROX and DCFDA assays it was found that AdipoRon reduced palmitate-induced ROS production. Image-IT DEAD, MTT and LDH assays all indicated that AdipoRon reduced palmitate-induced cell death. Palmitate significantly increased intracellular accumulation of S1P, whereas in the presence of AdipoRon there was increased release of S1P from cells to extracellular medium. It was also observed that direct addition of extracellular S1P prevented palmitate-induced ROS production and cell death, indicating that S1P is acting in an autocrine manner. Pharmacological approaches to enhance or decrease S1P levels indicated that accumulation of intracellular S1P correlated with enhanced cell death. CONCLUSION: This data indicates that increased extracellular levels of S1P in response to adiponectin receptor activation can activate S1P receptor-mediated signaling to attenuate lipotoxic cell death. Taken together these findings represent a possible novel mechanism for the protective action of adiponectin.